The trading profits of SOES bandits - Harris, Jeffrey H.; Schultz, Paul H. (Journal of Financial Economics, 1998)
SOES bandits are individual investors who use Nasdaq's Small Order Execution System (SOES) for day trading. Their average profit per trade is small, but they trade dozens or hundreds of times per week. Bandits usually establish a position before most market-makers have updated their quotes, and lay off the position at favorable prices through Instinet or SelectNet. It is noteworthy that they trade profitably with market-makers despite having less information. Bandits keep the profits and bear the losses from their trades. Thus they have greater incentives to trade well than the employees of market-making firms.